Boekbesprekings/Book Reviews (HTS teologiese studies, 2008)
Ephesians: Empowerment to walk in love for the unity of all in ChristThe stem cell debateDarwin and intelligent designThe fathers of the church: A comprehensive introductionSpiritual emotions: A psychology of Christian virtuesThe Bonhoeffer legacy post-holocaust perspectiveWondrously shelteredDietrich Bonhoeffer: A life in picturesA people's history of Christianity, Vol. 5 Reformation ChristianityDefeating depression: Real help for you and those who love youMartin Luther's message for us todayJurgen Moltmann Eine Lebensgeschichte, herausgegebn von W RaumA broad place: An authobiographyRender to God: New Testament understanding of the divine